2020
DOI: 10.3389/fpsyt.2020.562835
|View full text |Cite
|
Sign up to set email alerts
|

Personality Traits and Disorders in Adolescents at Clinical High Risk for Psychosis: Toward a Clinically Meaningful Diagnosis

Abstract: Aims: Recent meta-analytic data show that approximately 40% of individuals at clinical high risk for psychosis (CHR) receive at least one personality disorder (PD) diagnosis. Personality pathology could significantly influence CHR patients' prognosis and response to treatment. We aimed at exploring the PD traits of CHR adolescents, in order to outline a prototypic description of their most frequently observed personality characteristics.Methods: One hundred and twenty-three psychiatrists and psychologists used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 84 publications
1
8
0
Order By: Relevance
“…Although the results obtained can be considered promising, more studies would be needed. In this regard, Boldrini et al (2020) identified through the SWAP-200 the following prototypical characteristics of patients at high risk for psychosis: avoidance of social relationships, suspiciousness, obsessive thoughts, lack of psychological insight, dysphoric and overwhelming feelings of anxiety and depression, strange and abnormal reasoning processes or perceptual experiences, symptoms of depersonalization and derealization, and negative symptoms of avolition, abulia, blunted affectivity, and impaired role functioning. In addition, as stated by Sevilla-Llewellyn-Jones et al (2018) it is still not entirely clear to what extent personality may influence the development of psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…Although the results obtained can be considered promising, more studies would be needed. In this regard, Boldrini et al (2020) identified through the SWAP-200 the following prototypical characteristics of patients at high risk for psychosis: avoidance of social relationships, suspiciousness, obsessive thoughts, lack of psychological insight, dysphoric and overwhelming feelings of anxiety and depression, strange and abnormal reasoning processes or perceptual experiences, symptoms of depersonalization and derealization, and negative symptoms of avolition, abulia, blunted affectivity, and impaired role functioning. In addition, as stated by Sevilla-Llewellyn-Jones et al (2018) it is still not entirely clear to what extent personality may influence the development of psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…Given the high prevalence of personality disorders in ultra‐high‐risk patients (18% after 6 months, 22% after 1 year and 29% after 2 years to 36% after 3 years) compared to the relatively low rate of psychotic transition (Boldrini et al, 2019; Boldrini, Pontillo, et al, 2020a; Boldrini, Tanzilli, et al, 2020b; Fusar‐Poli et al, 2016; Sevilla‐Llewellyn‐Jones et al, 2018), intervention programs for at‐risk mental states patients should be supplements with personalized treatments that recognize, focus and treat maladaptive personality traits, to prevent transition to psychosis and promote psychological well‐being. Future research should investigate the relationship between psychopathological dimensions of personality and outcomes of early intervention programs for psychosis.…”
Section: Discussionmentioning
confidence: 99%
“…MBT-P, moreover, could be helpful in preventing ( 53 , 54 ) from the onset of full-blown psychosis through improved long-term social functioning ( 53 , 55 ). In addition, dysfunctional personality traits are particularly prevalent in this population ( 56 , 57 ), and an estimated 40% of this population has a personality disorder in comorbidity ( 50 ), findings that can justify the application of treatment.…”
Section: Discussionmentioning
confidence: 99%